Prevalence of fibromyalgia in a Brazilian series of patients with multiple sclerosis - Cinthia Thomas; Bianca Thais Schneider; Caroline Schiochet Verza; Gabriel Fassina; Laís Restel Weber; Marlinton Moreira; Paula Tormen Fusinato; Cassiano Mateus Forcelini (Arquivos de Neuro-Psiquiatria)
Background The prevalence of pain in patients with multiple sclerosis is remarkable. Fibromyalgia has been considered as one of the forms of chronic pain encompassed in multiple sclerosis, but data are restricted to studies from Europe and North America.